Change Unplanned into Planned Online Learning: An Effort to Follow Health Protocols at an Information Technology College During the Covid-19 Pandemic Period - M.J. Dewiyani Sunarto (Studies in Learning and Teaching, 2021)
The Covid-19 pandemic not only has negative impacts, but also positive impacts, one of those is the development of online learning. Online learning, of course, does not mean simply moving face-to-face encounters to virtual ones, as happened during the first semester of the Covid-19 pandemic. The problem to be solved in this study is how to change sudden/unplanned online learning in the first semester of the Covid-19 pandemic into planned online learning in the second semester based on theoretical studies, and to define if there are changes in student responses in the two consecutive semesters. The results obtained are a theoretical study for the formation of planned online learning, as well as an increase in the results of student responses via questionnaires which indicate progress in efforts to prepare unplanned online learning into planned online learning.